COVID-19: Using Social Media to Promote Mental Health in Medical School During the Pandemic - Han G. Ngo; Brianna L. Gibney; Paul Patel; Jennifer L. Nguyen (University Library System, University of Pittsburgh, 2020)
The Asian Pacific American Medical Student Association (APAMSA) is a national student organization that advocates for the health of the Asian American Pacific Islanders. In May 2020, our APAMSA chapter at Oakland University William Beaumont (OUWB) School of Medicine located in Michigan, USA hosted a virtual mental health campaign titled, "Socially Distant but Emotionally Connected: 6ft Closer During Quarantine." We reached out to medical students and faculty within the OUWB community to share their experiences during the initial phases of quarantine. Our goal was to create a space for everyone at OUWB to engage in meaningful conversations about mental health and support each other during the pandemic. The responses we received varied across numerous topics, including xenophobia, loneliness, and lack of motivation. Participants also followed up with words of encouragement for their peers and guidance on how to cope with social isolation. Our virtual campaign was very feasible and successful under the constraints of social distancing, and we urge other medical schools to implement their own mental health awareness initiatives to destigmatize the topic in their communities. General steps on how to start your own campaign include: collaborating with interest groups, deciding on social media platforms, and sharing with your community.